Closed-loop control systems – The quest for precision therapies for diabetes. Issue 5 (October 2017) - Xie, Mingqi; Aubel, Dominique; Fussenegger, Martin
Abstract: Diabetes mellitus is a complex metabolic disease characterized by insulin deficiency and chronically deregulated blood-glucose levels. Treatment strategies based on electronic artificial pancreas systems and human islet transplantations are already available to provide automated and closed-loop glycaemic control, but more sophisticated solutions are urgently needed to provide higher diagnostic accuracy, longer treatment duration, better quality of life and greater safety. In this review, we describe recent breakthroughs in stem cell research and synthetic biology, and critically discuss their future potential from the viewpoints of clinical applicability and marketability. Highlights: Latest advances in closed-loop diabetes therapies. Coverage of artificial pancreas systems. Description of lineage-control technologies for the differentiation of beta cells. Design and programming of mimetic beta cells.